Exploring the Disconnect Between Information Literacy Skills and Self-Estimates of Ability in First-Year Community College Students - Coates, Heather (Evidence Based Library and Information Practice, 2013)
Objective - To explore the relationships between information literacy (IL) test scores and self-estimated ability both prior to and after completing the test. Design - Information Literacy Test (ILT) with pre- and post-test surveys of self-estimated ability. Setting - Two community colleges: a small institution in a rural area and a large institution in an urban area. Subjects – First-year community college students enrolled in entry-level English courses. Methods – The authors conducted a replication study of their earlier work using a larger sample from two community colleges. Information literacy (IL) skills were assessed using the Information Literacy Test (ILT) developed and validated by researchers at James Madison University. During the spring and fall semesters of 2009 and 2011, the authors administered in a single session the ILT, pre-, and post-test survey instruments to 580 participants. Participants self-selected via sign-up sheet. The first hundred students to sign up per enrollment period were scheduled. Participants received incentives for participation, with an additional incentive offered for scoring in the top 15%. Main Results - The majority of students at both schools (95% at school 1, 80% at school 2) scored in the below-proficient range on the ILT, a few scored in the proficient range (5% at school 1, 20% at school 2), but no students scored in the advanced range. The mean of the few scores in the proficient range was closer to the below-proficient range (≤65%) than the advanced range (≥90%). For students at both schools, significant differences were found between their self-estimated and actual test score. While students at both schools adjusted their self-estimated scores downward after completing the ILT, post-test self-estimates remained significantly inflated in relation to their test performance. In particular, students scoring in the below-proficient range demonstrated a large and significant gap. The difference between the self-estimated comparisons to peers and actual scores was significant for students from both schools who scored in the below-proficient range. Only the proficient students at school 1 were able to accurately estimate their IL skill level. Most students completed the ILT remaining unaware of their poor performance. Conclusion – The study revealed a significant disconnect between students’ perceptions of their information literacy skills and their actual performance. Students scoring in the proficient range demonstrated a stronger post-test correction response than students scoring at below-proficient levels. Generally, the authors of the find that the results support the Dunning-Kruger Effect theory that people lacking skills in a particular domain demonstrate a miscalibration between self-estimated and actual skill. Specifically, it confirms that this effect occurs in the domain of information literacy. There is a need for tools to diagnose information literacy competence. Most students are unable to self-assess accurately and competency should not be assumed. Meeting the needs of this population will be challenging, given that they do not recognize the need for instruction or assistance.